Intelligent Traffic Monitoring System by Using ZIGBEE and VANET Technology - Lakshmi, YS Vijaya; Kumar, V. Jagadeesh; Raju, R. Kanaka (International Journal of Computer Sciences and Engineering, 2020)
The main objective of this proposal is to reduce the road accidents due to high speed of moving vehicles in traffic. In the current system the speed limiting boards are monitored by static in nature, due to which on any given day when there is high vehicular traffic moving with high speed there is a need of necessity to decrease the speed of vehicles below the permissible speed shown on the display board. The proposed system introduces the concept of Intelligent Traffic Monitoring System by using ZIGBEE technology along with VANET. According to the system, speed limit boards are erected to the current poles lying on the roads which will display the speed limit. Every area is designated with the set speed limit. When the vehicle passes by that area and there is a speed mismatch of the vehicle with the display board, speed will be recorded and further monitored at the next point and if it is still not decreased then a necessary action will be taken which may also lead to the cancellation of the license of the driver.